Cardiovascular event risk assessment in planned cardosurgery interventions - G. I. Sidorenko; S. M. Komissarova (Кардиоваскулярная терапия и профилактика)
Aim. To investigate quantitative assessment of myocardial, coronary and neuro-vegetative reserves in coronary heart disease (CHD) and chronic heart failure (CHF) patients before planned interventional myocardial revascularization, to objectivize peri-intervention complication risk. Material and methods. In total, 62 CHD patients with macrofocal cardiosclerosis and NYHA Functional Class (FC) III CHF were examined before planned interventional myocardial revascularization. Instrumental tests included: coronarography, echocardiography, 24-hour ECG monitoring, heart rate variability analysis, 6-minute walking test with short-term Holter monitoring. Results. Risk objectivization potential for peri-intervention cardiovascular complications is discussed. The authors propose to qualitatively assess cardiovascular system adaptation ability in clinical settings, in addition to traditional EUROSCORE system. Conclusion. The proposed qualitative adaptation reserve assessment, not complicating pre-intervention examination, not only evaluates risk level, but also provides insights on protection of the most vulnerable cardiovascular system components.